HUBUNGAN TINGKAT STRES DENGAN KESIAPAN DIRI SISWA SAAT KEMBALI BERSEKOLAH PASCA DARING PANDEMI COVID-19 DI SMA SWASTA YAPIM SIBIRU-BIRU TAHUN 2022 - Gurusinga, Mona Fitri; Hutagalung, Meta (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Officially informed that school will be held face-to-face students complain of stress about this, to achieve a level of readiness, physical and psychic conditions are needed that support each other's readiness in the learning process. To: Identify stress levels, and self-readiness in students when returning to school, Analyze the relationship between stress levels and students' self-readiness when returning to school post-online Types This study is an observational analytic with a go-sectional approach. This has a look at what was used to find the relationship between impartial variables and based variables. This research method can be done by using surveys, questionnaires, and interviews of strain tiers with students' self-readiness at mild pressure ranges of 31 people (forty three.7%), mild as many as 21 human beings (29.6%), weight as many as 15 humans (21.1%), and really heavy 4 human beings (5.6%) with a p-fee of zero.003 (.zero.1/2) so that Ha is time-honored this means that there is a stress relationship with students' self-readiness whilst returning to high school after the Covid-19 pandemic at Yapim Sibiru-biru private excessive college in 2022 There is a relationship between stress levels and students' self-readiness when they return to school after the COVID-19 pandemic at Yapim Sibiru-biru Private High School in 2022. Severe and moderate stress levels can trigger a person's self-readiness, especially in students changing the teaching and learning process which was previously online and then offline with strict health protocol rules at school, as well as from themselves and the environment.